(untitled) (International journal of artificial intelligence, 2026)
This research article examines the effectiveness of communicativeactivitiesin enhancing the speaking proficiency of secondary school students. Developingoral fluencyremains one of the most significant challenges for EFL (English as a ForeignLanguage)learners due to psychological barriers, such as speaking anxiety, and a lack of interactiveenvironments. The study was conducted at Secondary School No. 25 in the Kyzyltepadistrictofthe Navoiy region, involving a purposeful sample of 50 students fromthe 6th, 7th, and9thgrades. Following a qualitative action research design, the study implementedvariouscommunicative tasks, including role-plays, information-gap activities, and logical gameslike"Alibi." Data were collected through structured observation tables and teacher reflectionjournals over a four-week period. The results indicate that 70% of the participants (35students)demonstrated a measurable improvement in fluency, lexical diversity, and communicativeconfidence. The findings suggest that shifting from teacher-led instruction to student-centeredinteractive tasks effectively lowers the "affective filter" and fosters spontaneous languageproduction. The paper concludes with practical pedagogical recommendations for Englishteachers to integrate communicative strategies into the secondary education curriculuminUzbekistan.